Development of the Bejijong Majapahit Village Tourism Village as an Effort to Grow the Regional Tourism Sector in the Era of the Covid-19 Pandemic - Johan Chrisna Bintoro; Siti Sri Wahyuni; Ika Barokah Suryaningsih (UPT Penerbitan Universitas Jember, 2021)
Tourism Village is a form of creativity that arises from a surrounding phenomenon that has more appeal than other villages. One of the tourist villages is the Bejijong Majapahit Tourism Village. The Bejijong Majapahit Tourism Village has just received an Indonesian tourism village award in 2021. So this village continues to develop so that it can become a tourist village that is attractive to both local and foreign tourists. The purpose of this study was to find out how to develop the Bejijong Tourism village in the pandemic era. Bejijong Tourism Village has a lot of potentials that can be developed, however, since the pandemic this tourist village has experienced several problems, especially the reduced number of tourists. This study seeks to find a solution to this phenomenon, the researchers conducted a qualitative descriptive research method to analyze existing social phenomena. The author analyzes some of the obstacles and drivers of this phenomenon and then examines the development of what can be done to revive the village economy and tourism sector. The results of this study can be a recommendation for tourist villages to develop human resources and tourism digitization in every aspect such as ticketing,publishing,and homestay reservation. Keywords: Tourism Village, Bejijong Village, Developed, Pandemic, Digitization